Nucleocytoplasmic transport and processing of small nuclear RNA precursors. - Neuman de Vegvar, H E (1990)
We have analyzed the structures and locations of small nuclear RNA (snRNA) precursors at various stages in their synthesis and maturation. In the nuclei of pulse-labeled Xenopus laevis oocytes, we detected snRNAs that were longer than their mature forms at their 3' ends by up to 10 nucleotides. Analysis of the 5' caps of these RNAs and pulse-chase experiments showed that these nuclear snRNAs were precursors of the cytoplasmic pre-snRNAs that have been observed in the past. Synthesis of pre-snRNAs was not abolished by wheat germ agglutinin, which inhibits export of the pre-snRNAs from the nucleus, indicating that synthesis of these RNAs is not obligatorily coupled to their export. Newly synthesized U1 RNAs could be exported from the nucleus regardless of the length of the 3' extension, but pre-U1 RNAs that were elongated at their 3' ends by more than about 10 nucleotides were poor substrates for trimming in the cytoplasm. The structure at the 3' end was critical for subsequent transport of the RNA back to the nucleus. This requirement ensures that truncated and incompletely processed U1 RNAs are excluded from the nucleus.